2019
DOI: 10.4103/jfmpc.jfmpc_49_19
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and behaviors related to dietary salt and sources of dietary sodium in north India

Abstract: Sodium, an element needed for the normal human physiology is known to be associated with high blood pressure and other consequences if consumed in excess. The assessment of knowledge and behavior related to sodium that is consumed in the form of salt plays an important role in the control of cardiovascular diseases. To control the intake of sodium, dietary sources of sodium need to be identified. To address this, a community-based cross-sectional study was conducted among women aged 20 to 59 years in north Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
3
2
0
Order By: Relevance
“…More than 60% of the respondents in all countries, except Germany, considered salt reduction important which is in agreement with results from other international studies [ 24 , 25 , 27 ]. However, while global salt consumption exceeds the recommended maximum levels and many participants considered salt reduction important, only few were making deliberate efforts to reduce their intake, possibly because they underestimated their salt intake, as previously postulated [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than 60% of the respondents in all countries, except Germany, considered salt reduction important which is in agreement with results from other international studies [ 24 , 25 , 27 ]. However, while global salt consumption exceeds the recommended maximum levels and many participants considered salt reduction important, only few were making deliberate efforts to reduce their intake, possibly because they underestimated their salt intake, as previously postulated [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…This is the first survey that has investigated KAB related to salt and iodine in European and Asian population groups. The results revealed that the majority of participants in all countries were unable to recall or identify the daily maximum amount of salt recommended for adults, which is in line with a recent comprehensive review [ 24 ] and other recent studies [ 25 , 26 ]. Knowledge gaps with regard to the fact that children should consume less salt than adults were also evident in our study group, indicating that despite the self-reported interest of respondents in nutrition or previous attendance of nutrition classes, communication and education about salt-related issues has not been effective in the participating countries.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with past studies among high income (19) and Asian countries (20,21,33) , participants in this study were aware Dietary sodiumknowledge, attitudes and behaviours…”
Section: Discussionsupporting
confidence: 78%
“…Consistent with past studies among high income (19) and Asian countries (20,21,33) , participants in this study were aware of the relationships between excess Na consumption and non-communicable diseases, such as high blood pressure and heart disease. Participants were also highly aware of the link between excess Na and kidney disease, which was less known in some countries, such as Australia and Barbados (34,35) .…”
Section: Discussionmentioning
confidence: 65%
“…The Chinese Australian group had significantly lower salt-related knowledge than their counterparts in China. Compared with other ethnic populations, our participants had a higher awareness of the daily recommended salt intake than study participants in Ethiopia and Northern India, where only 1.8% and 5% of participants respectively were aware of the daily recommended salt intake [ 60 , 61 ]. However, over 87% of the participants in the Ethiopian study were aware of the increased risk of hypertension with a high salt intake.…”
Section: Discussionmentioning
confidence: 71%